Tensile behavior of a prefabricated Steel–UHPC composite deck system with notched perfobond strips. (1st October 2022) - Tan, Xingyu; Fang, Zhi; Peng, Zhongli; Zheng, Hui; Tang, Shoufeng; Liao, Yuan
Highlights: A Prefabricated steel–ultra-high-performance concrete (UHPC) composite deck (PSUCD) system equipped with notched perfobond strips (NPBLs) was proposed for better exploiting the high compressive strength of the UHPC in long-span cable-stayed bridges; Tensile tests were performed on seven full-scale composite panel specimens to identify the tensile behavior of the proposed deck system, including the cracking mode, strain distribution and tensile strengths; The effects of the types of shear connectors, the interfacial shapes of wet joints, and the number of NPBLs placed across the joint interfaces on the tensile behavior of the proposed deck system were elaborated; Considering the weakened tensile strength and sectional area ratio of joint interfaces, a prediction method for the crack widths at the wet joint interfaces in the PSUCD systems was developed and verified. Abstract: This paper proposes a prefabricated steel–ultra-high-performance concrete (UHPC) composite deck (PSUCD) system equipped with notched perfobond strips (NPBLs) for long-span cable-stayed bridges. Compared with the use of an ultra-thin UHPC overlay, the proposed deck system better leverages the high compressive strength of the UHPC. Seven full-scale composite panel specimens with varying details of joint interfaces and shear connectors are subjected to tensile tests. The experimental results reveal that compared with a monolithic UHPC layer, the tensile strengths of the UHPC layer at the initial and nominal cracking (corresponding to a maximum crack width of 0.05 mm) are reduced by 47 % and 64 %, respectively, when flat joint interfaces are introduced and by 16 % and 40 %, respectively, when the interfaces are rectangular-tooth-shaped. The higher steel reinforcing ratio derived from the use of NPBLs placed across the joint interfaces leads to a distinct improvement in the post-cracking performance of the wet joints. Considering the weakened tensile strength and sectional area ratio of the joint interfaces, a prediction method for the crack widths at the wet joints in PSUCD systems is developed, and its prediction accuracy is verified.